Tamibarotene in patients with acute promyelocytic leukaemia relapsing after treatment with all‐trans retinoic acid and arsenic trioxide. (24th July 2015) - Sanford, David; Lo‐Coco, Francesco; Sanz, Miguel A.; Di Bona, Eros; Coutre, Steven; Altman, Jessica K.; Wetzler, Meir; Allen, Steven L.; Ravandi, Farhad; Kantarjian, Hagop; Cortes, Jorge E.
Summary: Treatment of acute promyelocytic leukaemia (APL) with arsenic trioxide (ATO) and all‐ trans retinoic acid (ATRA) is highly effective first‐line therapy, although approximately 5–10% of patients relapse. Tamibarotene is a synthetic retinoid with activity in APL patients who relapse after chemotherapy and ATRA, but has not been studied in relapse after treatment with ATO and ATRA. We report on a phase II study of tamibarotene in adult patients with relapsed or refractory APL after treatment with ATRA and ATO ( n  = 14). Participants were treated with tamibarotene (6 mg/m 2 /d) during induction and for up to six cycles of consolidation. The overall response rate was 64% ( n  = 9), the rate of complete cytogenetic response was 43% ( n  = 6) and the rate of complete molecular response was 21% ( n  = 3). Relapse was frequent with 7 of 9 responders relapsing after a median of 4·6 months (range 1·6–26·8 months). The median event‐free survival (EFS) was 3·5 months [95% confidence interval (CI) 0–8·6 months] and the median overall survival (OS) was 9·5 months (95% CI 5·9–13·1 months). These results demonstrate that tamibarotene has activity in relapsed APL after treatment with ATO and ATRA and further studies using tamibarotene as initial therapy and in combination with ATO are warranted.